Knowledge and attitude of occupational health and safety among laboratory worker of Faculty of Medicine and Health Sciences and Faculty of Veterinary Medicine in University Putra Malaysia. . - M. S., Munisah; M. P., Muhammad Sufi; Siak, B. L.; Zainuddin, Huda; Syed Waseem Ahmad, Sharifah Roohi (Springer Verlag, 2011)
Introduction:Laboratory workers are exposed to variety of hazards that may affect their health and safety. Awareness of occupational safety and health (OSH) is important in preventing occupational injuries and diseases. The objective of this study was to assess the knowledge of OSH among laboratory workers in Faculty of Medicine and Health Sciences and Faculty of Veterinary Medicine, Universiti Putra Malaysia. Methods:A cross-sectional study was conducted on laboratory workers in the two faculties in Universiti Putra Malaysia.A pretested, self-administered questionnaire comprising of 5 sections including socio-demographic, OSH environment of the laboratory, exposure to the knowledge of OSH, knowledge of OSH and attitude of laboratory workers in the laboratory was distributed to all registered permanent laboratory workers in the faculties. Data entry and analysis was done using Statistical Package for Social Science (SPSS) version 18.Descriptive statistics on socio-demography and job factors were determined. Independent t-test and chi-squared test were used to test associations. Correlation between attitude and knowledge on OSH was computed. Results: The response rate was 64.42% (67 laboratory workers). The overall level of knowledge on OSH was moderate, with a mean score of 62%. A larger proportion of female respondents (51.5%) showed good OSH knowledge compared to male respondents (14.7%) and the difference was statistically significant (10.288, 1; p<0.01). Majority of the respondents (73.7%) who worked in a poor OSH laboratory environment had poor attitude level towards OSH (χ2=7.135, df=1; p=0.008). There was a moderate positive correlation between knowledge and attitude on OSH (r=0.4, p<0.01). Knowledge explains 16% of the variance in level of attitude towards OSH among laboratory workers. Conclusion: Knowledge of OSH among laboratory workers was moderate and is associated with gender and OSH environment in the workplace. A greater effort to promote OSH knowledge among the laboratory workers is needed to ensure their safety and health in workplace.